Menyoal Kegentingan dan Pasal Impunitas Dalam Perppu Corona - Siti Nurhalimah (UIN Syarif Hidayatullah Jakarta, 2020)
Abstract:The weakening of business activities due to the Corona pandemic has reduced state revenues, while increasing the cost of state expenditure (Economic Instability). If it is not handled carefully and immediately, it is feared that this pandemic will cause a long-term effect and impact on the sustainability of national economic instability. The government then issued regulations regarding financial hurdles and stability of the country's financial system through the